TAXONOMY, ECOLOGICAL SIGNIFICANCE AND PHYTOCHEMICAL (CARBOHYDRATE) ANALYSIS OF SCHOENOPLECTUS LACUSTRIS SUBSP. HIPPOLYTI (Scientific journal of the Fergana State University, 2026)
This article examines the taxonomy, ecological significance, and phytochemical (carbohydrate) composition of Schoenoplectus lacustris subsp. hippolyti (Cyperaceae). The subspecies was found to be distributed across several regions of Uzbekistan, mainly in wet habitats and along water bodies. Its ecological role, particularly in natural water purification and the stabilization of hydroecosystems, is highlighted.Chemical composition was analyzed using high-performance liquid chromatography (HPLC, Agilent 1100). The results revealed the presence of three carbohydrates in the plant material: fructose (0.07 mg/g), glucose (0.05 mg/g), and maltose (0.06 mg/g), whereas sucrose was not detected. The total soluble carbohydrate content amounted to 0.18 mg/g dry weight.The findings indicate that S. lacustris subsp. hippolyti accumulates relatively low levels of soluble carbohydrates, which may be associated with its physiological adaptation to aquatic environments. At the same time, the presence of biologically active compounds confirms its potential as a promising subject for ecological and pharmaceutical studies.